The Monetary Approach to Exchange Rate in an Efficient Foreign Exchange Market: Tests Based on Volatility - HUANG, ROGER D. (Journal of Finance, 1981)
ABSTRACT The variance bounds on exchange rate movements implied by the monetary approach to exchange rate in an efficient foreign exchange market is shown to be violated by sample data. The paper also presents evidence showing that the forecast errors implied by the monetary model can be forecasted using historical data. The results are interpreted to suggest either the incompatibility of the monetary approach with sample data, or an inefficient foreign exchange market or both.